Komparasi Kewenangan Eksekutif Dalam Pembentukan Undang-Undang Pada Sistem Pemerintahan Presidensil: Antara Indonesia Dengan Amerika - Dania Shofi Maziyah; Xavier Nugraha (Jurnal Selat, 2020)
Each country is unique in running its system of government. One of these uniqueness is related to the executive's authority in the formation of laws, where even though the State both uses a presidential system of government, there are differences in authority. This difference can be seen in Indonesia and America, where even though these countries both use a presidential system of government, there are differences in executive authority. In order to understand the ratio legis, there are differences, even though the 2 (two) countries both use presidential government systems, this research was conducted. The formulation of the problems in this study are 1) the characteristics of the presidential government system and 2) the authority of the president as an executive in the formation of laws in the presidential system in Indonesia and the United States. This research is a legal research with a statutory approach, a conceptual approach, and a comparative approach.